Selective vulnerability of stellate cells to gut dysbiosis: neuroanatomical changes in the medial entorhinal cortex - Mydeen, Ayishal B.; Nakhal, Mohammed M.; Nafees, Faheema; Almazrouei, Reem; Alkamali, Rasha; Alsulaimi, Mahra; Aleissaee, Omar; Alzaabi, Abdulrahman; Alfahim, Mohamed; Almansoori, Hamad; BaniYas, Shamsa; Al Houqani, Shaikha; et al. (Frontiers in Neuroanatomy, 2025)
IntroductionThe gut microbiota plays a critical role in regulating brain structure and function via the microbiota–gut–brain axis. Antibiotic-induced gut dysbiosis (AIGD) has been linked to neuroanatomical changes and cognitive deficits. However, its impact on neuronal morphology in layer II of the medial entorhinal cortex (mECII), a region central to spatial memory, remains poorly understood. This study examines how AIGD affects dendritic architecture in mECII stellate and pyramidal island cells.MethodsMice received a broad-spectrum oral antibiotic cocktail to induce AIGD. Gut microbiota composition was analyzed using 16S rRNA sequencing. Golgi-stained neurons in mECII were assessed for dendritic complexity via Sholl analysis. Iba1 staining evaluated microglial activation in mECII. Intestinal sections were stained with NeuN and CD8 to assess enteric neuron density and inflammation. Microbial abundance was correlated with dendritic parameters.ResultsAIGD resulted in significant dysbiosis, including depletion of butyrate-producing taxa (Roseburia, Faecalibacterium) and enrichment of proinflammatory bacteria (Clostridium, Salmonella, Enterococcus). Stellate cells showed marked dendritic atrophy, while pyramidal island cells were unaffected. Dendritic complexity positively correlated with Roseburia hominis and negatively with Enterococcus faecalis. No microglial activation was detected in mECII, but CD8 + T-cell infiltration increased in the gut without changes in NeuN-labeled enteric neurons.DiscussionThese findings suggest AIGD selectively alters mECII stellate cell morphology through peripheral immune signaling or microbial metabolites, independent of local microglial activation. This study highlights the role of gut microbiota in shaping neuronal architecture and supports microbiome-targeted strategies to counteract dysbiosis-associated neuroanatomical changes.